1997
DOI: 10.1128/jb.179.1.17-23.1997
|View full text |Cite
|
Sign up to set email alerts
|

The alternative sigma factor sigma28 of Legionella pneumophila restores flagellation and motility to an Escherichia coli fliA mutant

Abstract: Gene expression in Legionella pneumophila, the etiological agent of Legionnaires' disease, can be controlled by alternative forms of RNA polymerase programmed by distinct factors. To understand the regulation of L. pneumophila flagellin expression, we cloned the factor (FliA) of RNA polymerase responsible for the transcription of the flagellin gene, flaA. FliA is a member of the 28 class of alternative factors identified in several bacterial genera. The gene fliA has been isolated from an expression library of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
48
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 47 publications
3
48
0
Order By: Relevance
“…flaA) (Albert-Weissenberger et al 2010;Brüggemann et al 2006;Jacobi et al 2004;Heuner and Albert-Weissenberger 2008). It is known that L. pneumophila rpoN, fleQ, fliA and flaA mutant strains are non-flagellated and non-motile (Heuner et al 1995;Heuner et al 2002;Heuner et al 1997;Jacobi et al 2004;Molofsky et al 2005). Conflicting data suggested different regulation mechanisms in strains Corby and Paris for fliA expression.…”
Section: Introductionmentioning
confidence: 99%
“…flaA) (Albert-Weissenberger et al 2010;Brüggemann et al 2006;Jacobi et al 2004;Heuner and Albert-Weissenberger 2008). It is known that L. pneumophila rpoN, fleQ, fliA and flaA mutant strains are non-flagellated and non-motile (Heuner et al 1995;Heuner et al 2002;Heuner et al 1997;Jacobi et al 2004;Molofsky et al 2005). Conflicting data suggested different regulation mechanisms in strains Corby and Paris for fliA expression.…”
Section: Introductionmentioning
confidence: 99%
“…As most of the genome of L. pneumophila has already been sequenced (http://genome3.cpmc.columbia .edu/ϳlegion/index.html), we looked for all the genes that have homology to known sigma factors and found that L. pneumophila contains homologs to at least six sigma factors (RpoD, RpoH, RpoF, RpoE, RpoS, and RpoN). The promoter sequence recognized by two of these sigma factors in L. pneumophila is already known (2,22). RpoH and RpoF recognize sequences similar to the ones recognized by their E. coli homologs (CTTGAAA [11 to 16]CCCATnT for RpoH [n ϭ A, G, T, or C] and TAAA [15]GCCGATAA for RpoF).…”
Section: Vol 184 2002 Regulatory Elements Of the L Pneumophila Icmmentioning
confidence: 99%
“…Previous reports suggest that the expression of flagella is temperature regulated, since it is repressed at temperatures higher than 37°C (36). Recently, we demonstrated that the expression of the flaA gene is regulated at the transcriptional level (24) by the alternative 28 factor (FliA) and probably by FlaR, a regulator of the LysR family (25). Moreover, the complex flagellum expression and assembly seems to be coordinatively regulated with other virulence-associated traits (6,16,38,40).…”
mentioning
confidence: 99%